Tracing the Trajectory of Islamic Stock Research (1989–2025): Insights from a Scopus-Based Bibliometric Analysis - Saifullah, Muhammad Fahmi; Apriantoro, Muhamad Subhi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
Research on Islamic stocks has grown significantly in recent decades, yet focused bibliometric analyses specifically using the term “Islamic stock” remain scarce. Existing studies often adopt broader themes like “Islamic finance” or “Islamic capital market,” which may overlook the nuanced evolution of Islamic stock research. This study aims to conduct a comprehensive bibliometric analysis of 1,050 documents indexed in Scopus between 1989 and 2025. The data were processed using Biblioshiny, VOSviewer, and Microsoft Excel to identify publication trends, citation dynamics, influential authors and sources, and thematic research clusters. The findings reveal a steady annual growth rate of 5.96%, with dominant contributions from Malaysia, Indonesia, and Saudi Arabia. Cluster analysis identified four main research themes: Islamic Stock Market, Banking and Economic Performance, Financial Markets and Investment, and Risk Management and Financial Assets. Recent research trends increasingly address topics such as bitcoin, COVID-19, and geopolitical risk, reflecting the expanding scope and relevance of Islamic stock research in global financial discourse. This study contributes to the literature by providing a focused thematic map of Islamic stock scholarship, highlighting knowledge gaps and potential future research directions for academics, policymakers, and ethical investors.